Integrated analysis of the ecotoxicological and genotoxic effects of the antimicrobial peptide melittin on Daphnia magna and Pseudokirchneriella subcapitata. (August 2015) - Galdiero, Emilia; Maselli, Valeria; Falanga, Annarita; Gesuele, Renato; Galdiero, Stefania; Fulgione, Domenico; Guida, Marco
Abstract: Melittin is a major constituent of the bee venom of Apis mellifera with a broad spectrum of activities. Melittin therapeutical potential is subject to its toxicity and the assessment of ecotoxicity and genotoxicity is of particular interest for therapeutic use. Here we analyzed the biological effects of melittin on two aquatic species, which are representative of two different levels of the aquatic trophic chain: the invertebrate Daphnia magna and the unicellular microalgae Pseudokirchneriella subcapitata . The attention was focused on the determination of: i) ecotoxicity; ii) genotoxicity; iii) antigenotoxicity. Our main finding is that melittin is detrimental to D. magna reproduction and its sub-lethal concentrations create an accumulation dependent on exposition times and a negative effect on DNA. We also observed that melittin significantly delayed time to first eggs. Moreover, results showed that melittin exerted its toxic and genotoxic effects in both species, being a bit more aggressive towards P. subcapitata . Graphical abstract: Highlights: We examine ecotoxicity to study how AMPs affect the environment. We examine genotoxicity in order to analyze the damages to the DNA. We examine the antigenotoxicity in order to verify DNA repair ability of the cells. Possible therapeutical applications of AMPs depend on assessment of ecotoxicity. Abstract : Melittin exerts its dose dependent toxic and genotoxic effects on both indicators; no toxicity is found at concentrations that may typically reach the environment.